Dynamics of Child Development : Analysis of a Longitudinal Cohort in a Very Low Income Country - Galasso, Emanuela (World Bank, Washington, DC, 2017)
Longitudinal patterns of child development and socioeconomic status are described for a cohort of children in Madagascar who were surveyed when they were 3–6 and 7-10 years old. Substantial wealth gradients were found across multiple domains: receptive vocabulary, cognition, sustained attention, and working memory. The results are robust to the inclusion of lagged outcomes, maternal endowments, measures of child health, and home stimulation. Wealth gradients are significant at ages 3–4, widen with age, and flatten out by ages 9-10. For vocabulary and sustained attention, the gradient grows steadily between ages three and six; for cognitive composite and memory of phrases, the gradient widens later (ages 7-8) before flattening out. These gaps in cognitive outcomes translate into equally sizeable gaps in learning outcomes. Between 12 and 18 percent of the predicted gap in early outcomes is accounted for by differences in home stimulation, even after controlling for maternal education and endowments.